Mood and Modality Analyses in Investigating Ideology of News About Indonesia in BBC World Webnews - Supatmiwati, Diah; Manda, Martin L.; Jihad Saleh, Noer; Makka , Mustafa (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
The primary aim of this study is to investigate the influence of ideology on news. The goals are to determine the interpersonal characteristics of the text and to link them to the ideologies that they can realize. The clause's mood structure is the means by which the fundamental differences are realized at the lexicogrammatical level within the contextual register variable of Tenor. Specifically, participants in an interaction encode their perception (or at least their ostensible perception) of both their relationships with others and the social and situational sense in which the interaction takes place through choices of mood elements such as topic and finite. There is a close complementarily between mood and modality and it is for this reason that the two systems have been analyzed together. Finally, the findings relate to the overall meaning-making and ideology-conveying resources of the text as a whole. The selected webnews consist in a set of texts. They were English articles with the general purpose to observe how Indonesian was portrayed in the BBC International Website or by the world.